2020
DOI: 10.1136/bmjopen-2020-038621
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions to improve the patient experience of colonoscopy under moderate or no sedation: a systematic review protocol

Abstract: IntroductionThe patient experience is a critical dimension of colonoscopy quality. Sedative and analgesic drugs are commonly used to improve the patient experience of colonoscopy, with predominant regimens being deep sedation, typically achieved with propofol, and moderate sedation, typically achieved with an opioid and a benzodiazepine. However, non-pharmacological interventions exist that may be used to improve patient experience. Furthermore, by identifying non-pharmacological interventions to increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We designed and reported this scoping review in accordance with the Arksey and O’Malley framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (online supplemental file 1). 16 17 The protocol was published18 and pre-registered as a systematic review (PROSPERO CRD42020173906). Substantial heterogeneity in the interventions and study outcomes reported among a large number of studies precluded a quantitative meta-analysis and would make qualitative synthesis following systematic review methodology suboptimal for comparing features across the included studies that are unique to the study question (eg, detailed assessments of outcome types).…”
Section: Methodsmentioning
confidence: 99%
“…We designed and reported this scoping review in accordance with the Arksey and O’Malley framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (online supplemental file 1). 16 17 The protocol was published18 and pre-registered as a systematic review (PROSPERO CRD42020173906). Substantial heterogeneity in the interventions and study outcomes reported among a large number of studies precluded a quantitative meta-analysis and would make qualitative synthesis following systematic review methodology suboptimal for comparing features across the included studies that are unique to the study question (eg, detailed assessments of outcome types).…”
Section: Methodsmentioning
confidence: 99%